Title "Dialectical Variations In The English Spoken In The Southern United States: A Comprehensive Study" - Azimov Shokhrukh (Western European Studies, 2024)
This study delves into the distinct linguistic features of English as spoken in the Southern United States, a region known for its rich linguistic diversity. The primary focus is on identifying and analyzing the phonological, syntactic, and lexical variations that characterize Southern American English. Employing a mixed-methods approach, the research incorporates both qualitative and quantitative analyses, drawing data from a diverse sample of speakers across various Southern states.Through detailed phonological examination, the study identifies characteristic patterns in accent and pronunciation unique to the region. It also explores syntactic variations, highlighting differences in sentence structure and grammatical usage compared to Standard American English. Additionally, the research uncovers a range of lexical peculiarities, including region-specific words and idioms, contributing to the distinct identity of the Southern dialect. The findings of this study offer a comprehensive overview of the linguistic idiosyncrasies present in Southern American English. By documenting these variations, the research contributes to the broader understanding of dialectical diversity in the English language, providing valuable insights for linguists, educators, and scholars interested in sociolinguistics and regional dialectology.
Keywords: Southern American English; Linguistic Diversity; Dialectal Variation